IMPLEMENTASI AKAD SYARIAH DALAM PRAKTIK PERBANKAN ISLAM DI INDONESIA - Ananda Fadil Rassya Saputra; Aqila Judya Shafwa; Rohmatul Umam (Taksasila Edukasi Insani, 2025)
This research examines the use of sharia contracts in Indonesian Islamic banking practices, focusing on the legal, financial, and religious facets of Islamic law. The primary goal is to examine the use of several Islamic contracts in actual financial transactions, including mudharabah, musyarakah, murabahah, ijarah, qardhul hasan, wakalah, kafalah, salam, and istisna, as well as how the hadith validates their validity. This study employed a normative legal method and a literature survey to qualitatively analyze both classical and modern sources, including national regulatory systems. The findings demonstrate that while the use of Islamic contracts improves equity, openness, and risk sharing, practical compliance, legal harmonization, and public literacy issues make implementation difficult. Strengthening regulatory congruence, boosting stakeholder education, and bolstering the sharia supervisory system are among the recommendations made to guarantee the integrity of Islamic banking operations. In line with Islamic principles, this study advances our knowledge of Islamic contracts as a crucial tool for creating a just and long-lasting financial system. Keywords : Islamic banking, Islamic contract, jurisprudence, sharia compliance, transaction